PERFORMANCE EVALUATION OF BRIDGE 5 CAWANG INTERCHANGE AT JAKARTA INTRA URBAN TOLLWAY - Afifi, Ahmad
The standard code of planning and loading bridges in Indonesia has undergone several changes, especially in the earthquake load planning aspect, with the latest changes in 2016, namely SNI 2833:2016 and SNI 1725:2016. With this change in standard codes, bridges that were already operating in Indonesia before 2016 needed to be evaluated on their structural performance. In this thesis, the bridge evaluated with the latest standard codes, namely Bridge 5 Cawang Interchange at Jakarta Intra Urban Tollway which has been built since 1987. The evaluation results show that the axial-bending capacity of the bridge pier elements is not able to carry loads with the latest standard codes in extreme boundary conditions. In addition, the required area of confinement reinforcement on the bridge pier elements does not meet the minimum reinforcement requirements. Furthermore, the performance evaluation of the bridge structure is carried out by using static pushover analysis (NSPA) on the pier P3 element for loading the longitudinal direction of the bridge, resulting in a performance level in Operational - Life Safety (O-LS) conditions with a drift of 1.56%. Besides, performance evaluation carried out by dynamic analysis (NLTHA) on the pier P3 element for loading the longitudinal direction of the bridge, resulting in a performance level which is the same as the NSPA result with a drift of 1.46%. Ultimately, when the structural retrofitting model is applied to the P3 pier element with RC-jacketing fc' 25 MPa with a thickness of 100 mm and additional longitudinal reinforcement of 72 D29, the P3 capacity is expected to increase by 49% from the initial capacity and the performance level will decrease to the Operational level (O) with a drift of 1%.